Efficacy and safety of antiseizure medication in post-stroke epilepsy. (August 2022) - Winter, Yaroslav; Uphaus, Timo; Sandner, Katharina; Klimpe, Sven; Stuckrad-Barre, Sebastian von; Groppa, Sergiu
Abstract: Background: Specific antiseizure medications (ASM) would improve the outcome in post-stroke epilepsy (PSE). The aim of this multicenter observational study was to compare different antiseizure monotherapies in PSE. Methods: We collected the data from 207 patients with PSE who did not change their initial antiseizure monotherapy during the period of 12 months. Efficacy was assessed by a standardized three month seizure frequency and seizure freedom. Safety was estimated by the reported side effects. Results: The mean three month seizure frequency was 1.9 ± 3.1 on eslicarbazepine, 2.1 ± 3.2 on lacosamide, 3.4 ± 4.4 on levetiracetam, 4.3 ± 6.8 on lamotrigine, and 5.1 ± 7.3 on valproate ( p  < 0.05 for eslicarbazepine or lacosamide in comparison with levetiracetam, lamotrigine and valproate, respectively). The lowest seizure frequency and the highest seizure freedom was observed on ASMs acting via the slow inactivation of sodium channels in comparison to other mechanisms of action (0.7 ± 0.9 vs 2.2 ± 2.4, p  < 0.01). Among side effects, the most frequently reported were vertigo (25%) and tiredness (15.9%). They were similar in all investigated groups of ASM. The independent factors increasing seizure frequency that were identified in multiple regression analyses were increased size of infarction, cortical involvement, hemorrhagic transformation, neurological deficits at admission and functional impairment. Administration of ASM with the mechanism of action via the slow inactivation of sodium channels was an independent factor decreasing the seizure frequency. Conclusion: Our data show that antiseizure medications acting via the slow inactivation of sodium channels, such as lacosamide and eslicarbazepine, are well tolerated and might be associated with better seizure control in PSE.